(untitled) (Journal of the College of Basic Education, 2022)
This research investigates whether the flipped learning can lead students to increased learning grammar outcomes in EFL contexts in Iraq. (88) Students were used to determine any differences in students’ achievement that might be associated with the flipped approach . The efficiency of the flipped approach on students’ success with grammar-student learning results was assessed with grammar pretest and posttest. Flipped classrooms change the conventional way of teaching by shifting what students do in school and at home. The outcomes pointed to that students were helpful achieved towards implementing the flipped classroom, and also that it may lead to increased learning of grammar. The study was performed with a quasi-experimental design. While the experimental group received the course through flipped learning , control group did not use learning strategies in the flipped classroom . The results indicated that flipped learning strategies positively affected the development of foreign language in the grammar tests’ outcomes